2017
DOI: 10.3892/ol.2017.5561
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors of long-term outcome in surgically resectable pancreatic neuroendocrine tumors: A 12-year experience from a single center

Abstract: The present study was performed to assess the prognostic factors with respect to patient survival and clinicopathological characteristics for patients who underwent surgery for pancreatic neuroendocrine tumors (PNETs). A retrospective review of patients pathologically diagnosed with PNETs at the First Affiliated Hospital, Zhejiang University School of Medicine (Hangzhou, Zhejiang, China) between September 2002 and September 2013 was conducted. The clinicopathological findings, overall survival (OS) rate and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
3
9
0
Order By: Relevance
“…Tumor factors that exhibit no any effect on the disease recurrence were found to be tumor size, location, angio-invasion and gross invasion to other viscera as type of operation that is performed and postoperative chemotherapy. This study revealed significant association between the disease recurrence with tumor grade (Pvalue 0.027), lymph node involvement (P-value 0.027) and tumor stage (P-value 0.017), which is near to the results achieved by other authors [32,33]. Among patient's variables that impact on survival jaundice alone as a presenting symptom left significant effect on survival with a (P-value 0.018) with the rest of the patients factors have no significant role on survival.…”
Section: Discussionsupporting
confidence: 83%
“…Tumor factors that exhibit no any effect on the disease recurrence were found to be tumor size, location, angio-invasion and gross invasion to other viscera as type of operation that is performed and postoperative chemotherapy. This study revealed significant association between the disease recurrence with tumor grade (Pvalue 0.027), lymph node involvement (P-value 0.027) and tumor stage (P-value 0.017), which is near to the results achieved by other authors [32,33]. Among patient's variables that impact on survival jaundice alone as a presenting symptom left significant effect on survival with a (P-value 0.018) with the rest of the patients factors have no significant role on survival.…”
Section: Discussionsupporting
confidence: 83%
“…Present organ metastasis might indicate low overall survival of pNENs according to the data provided by 3 of 4 articles 13 , 20 , 27 and the combined data (Table 4 , Fig. 3D ).…”
Section: Resultsmentioning
confidence: 85%
“…2 of 6 studies 13 , 21 suggested that poor prognosis of pNENs was associated with advanced G stage, while 4 of 6 studies 12 , 20 , 26 , 27 had no statistical difference between people with high or low G stage. Our pooled data showed that patients with advanced G stage were prone to suffer from pNENs (Table 4 , Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Compared with pancreatic ductal adenocarcinoma, pNETs have better long-term survival rates [ 5 , 6 ]. Recently, several large cohort studies found that lymph node involvement, tumor stage and grade, tumor size and Ki-67 index scores could predict the prognosis of pNETs [ 5 7 ]. However, some patients with small tumors or tumors with a low World Health Organization (WHO) grade (grade 1 or 2) may exhibit liver or lymph node metastasis and have a poor prognosis [ 8 ].…”
Section: Introductionmentioning
confidence: 99%